Immunosuppressive property of submandibular lymph nodes in patients with head and neck tumors: differential distribution of regulatory T cells - Daiju Sakurai (BMC Research Notes, 2018)
Abstract Objective Different sensitizations and immune responses are thought to be induced in response to antigens at different mucosal sites between the oral floor and nose. The aim of this study was to investigate differences in the distributions of lymphocyte subsets in the submandibular (SM) and upper jugular (UJ) lymph nodes (LNs), which are supposed to be regional LNs of the oral floor and nasal mucosa, respectively. SMLNs and UJLNs were collected from patients with head and neck tumors who underwent surgical resection. The populations of T cells, Natural Killer (NK) cells, Natural Killer T (NKT) cells, regulatory T cells (Tregs) and dendritic cells (DCs) in LNs without metastasis were analyzed by flow cytometry. The high-affinity IgE receptor (FcεRI) expression of LN cells were also evaluated. Results The proportions of CD4+CD25+Foxp3+ Tregs, CD4+CD45RA−Foxp3high effector Tregs and FcεRIα+CD33+CD11c+ DCs were significantly larger in SMLNs compared with UJLNs, while those of CD3+ T cells, CD3−CD56+ NK cells, CD3+Vα24+Vβ11+ NKT cells, and CD123+CD303+ DCs did not show any significant differences between SMLNs and UJLNs. The differential distributions of CD4+CD25+Foxp3+ Tregs were observed regardless of tumor region, LN metastasis and clinical staging. These data indicate that SMLNs may have immunosuppressive properties compared with UJLNs.